Executive Character, Leverage, Political Connection, and Profitability on Tax Avoidance: Moderated By Institutional Ownership - Azra, Nadia Nostiva; Rahma, Anita Ade (GOVERNORS, 2023)
The study examines the impact of executive character, leverage, political connections, and profitability on tax avoidance moderated by institutional ownership in manufacturing companies listed on the Indonesian Stock Exchange (BEI) from 2017-2021. The study uses quantitative data, which is used to prove the cause-and-effect relationship between independent variables, namely, executive character, leverage, political connection and profitability to the dependent variable. The results support the efficient transaction hypothesis theory, which suggests that RPT is profitable but reduces corporate tax aggressiveness. Leverage and profitability are proven to have a significant influence on tax avoidance. Meanwhile, executive character and political connections are the opposite, namely they do not have a significant effect on tax avoidance. Debt levels and profits have an important role in tax avoidance. the existence of institutional ownership also does not have a significant impact on tax avoidance. Likewise, institutional ownership is unable to strengthen the relationship between executive character, political connections and profitability with tax avoidance. However, unlike leverage, institutional ownership is able to strengthen the relationship between leverage and tax avoidance. So it is clear that the level of debt certainly needs to be the main monitoring if the company is going to carry out tax avoidance. The findings provide valuable insights for companies looking to improve their tax preventive strategies.